Islamic Republic of Iran : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1995)
This paper reviews economic developments in Iran during 1990-95. The growth rate of real GDP declined from an average of 11 percent in 1990/91-1991/92 to 2.7 percent in 1994/95. This decline was associated with developments in both the oil and non-oil sectors, such as capacity constraints in the industrial sector; adverse movement in international oil prices; reduction in oil export volumes; and quantitative import restrictions, which adversely affected industries that depended on imported inputs. The real value added in the oil sector declined by 5.6 percent in 1994/95.